Contribution of opsins and chromophores to cone pigment variation across populations of Lake Victoria cichlids. Issue 2 (29th December 2021) - Wilwert, Elodie; Etienne, Rampal S.; van de Zande, Louis; Maan, Martine E.
Abstract: Adaptation to heterogeneous sensory environments has been implicated as a key parameter in speciation. Cichlid fish are a textbook example of divergent visual adaptation, mediated by variation in the sequences and expression levels of cone opsin genes (encoding the protein component of visual pigments). In some vertebrates including fish, visual sensitivity is also tuned by the ratio of vitamin A1 /A2 –derived chromophores ( i.e ., the light‐sensitive component of the visual pigment bound to the opsin protein), where higher proportions of A2 cause a more red‐shifted wavelength absorbance. This study explores the variation in chromophore ratios across multiple cichlid populations in Lake Victoria, using as a proxy the expression of the gene Cyp27c1, which has been shown to regulate the conversion of vitamin A1 into vitamin A2 in several vertebrates. This study focuses on sympatric Pundamilia cichlids, where species with blue or red male coloration co‐occur at multiple islands but occupy different depths and consequently different visual habitats. In the red species, we found higher cyp27c1 expression in populations from turbid waters than from clear waters, but there was no such pattern in the blue species. Across populations, differences between the sympatric species in cyp27c1 expression had a consistent relationship with species differences in opsin expression patterns, but the red/blue identity reversed between clear and turbid waters. To assess the contribution of heritable vs . environmental causes of variation, we tested whether light manipulations induce a change in cyp27c1 expression in the laboratory. We found that cyp27c1 expression was not influenced by experimental light conditions, suggesting that the observed variation in the wild is due to genetic differences. Nonetheless, compared to other cichlid species, cyp27c1 is expressed at very low levels in Pundamilia, suggesting that it may not be relevant for visual adaptation in this species. Conclusively, establishing the biological importance of this variation requires testing of actual A1 /A2 ratios in the eye, as well as its consequences for visual performance.